PERKEMBANGAN NANOSAINS DAN NANOTEKNOLOGI: FENOMENA DARI SIFAT FISIKA DAN KIMIA - Paramita, Safira Arta; Priyono, Priyono (BERKALA FISIKA, 2024)
Nanoscience breakthroughs in almost every field of science and nanotechnologies make life easier in this era. Interest in nanomaterials and especially nanoparticles has exploded in the past decades primarily due to their novel or enhanced physicochemical properties compared to bulk material. Nanoscience and nanotechnology represent an expanding research area, which involves structures, devices, and systems with novel properties and functions due to the arrangement of their atoms on the 1–100 nm scale. These extraordinary properties have created a multitude of innovative applications in the fields of medicine and pharma, electronics, agriculture, chemical catalysis, food industry, and many others. We try to provide a comprehensive overview of the different classes of nanoparticles and their novel or enhanced physicochemical properties including mechanical, thermal, magnetic, electronic, optical, and catalytic properties. We hope that this makes the many different methods more accessible to the readers, and to help with identifying the proper methodology for any given nanoscience problem.